Stigma, housing and identity after prison. - Keene, Danya E; Smoyer, Amy B; Blankenship, Kim M (The Sociological review, 2018)
Existing research suggests that individuals who are released from prison face considerable challenges in obtaining access to safe, stable, and affordable places to live and call home. This article draws on repeated qualitative interviews (conducted every 6 months over a period of 3 years) with 44 formerly incarcerated individuals, to understand how these individuals experience the search for a home after their prison release. The interviews show that the quest for a home is central to participants' reintegration projects as they seek to establish themselves as 'decent' and economically self-sufficient citizens, and shed stigmatized identities associated with incarceration, poverty, homelessness, and place. Interviews also suggest that their quest for a home is an arduous one as they encounter numerous barriers to housing arising from both structural and interpersonal forms of incarceration stigma. Somewhat paradoxically, the challenges that they face in accessing housing seem to hinder their ability to shed the stigmatized identities associated with their incarceration. Ultimately, the narratives presented here show how stigma can restrict access to a valuable material and symbolic resource (housing), resulting in ongoing stigmatization, and contributing to the enduring and discrediting mark of incarceration. In this way, the study illustrates how stigma that is enacted by both individuals and the state, that is embodied in place, and that is internalized and managed by stigmatized individuals themselves, can work to reproduce power and serve as justification for inequality.
Keywords: Housing; Incarceration; Spatial stigma; dept.swk; peer-reviewed

Ping-pong housing: Women’s post-incarceration trajectories - Smoyer, Amy B; Keene, Danya E; Oyola, M.; Hampton, A (Affilia, 2020)
This study examines the post-incarceration housing experiences of 33 women. Using Residential Timeline Followback methodology, participants were asked to report where they lived at arrest and every location since their release. Follow-up questions asked women to describe these locations, who they lived with, how much they paid, and whether or not they felt safe. Demographic information and criminal justice history were recorded. The data paint a complicated picture of social and community resources, persistence, and struggle. Housing assets lost at incarceration were difficult to recover. Most women bounced between various locations, relying heavily on short-term subsidized congregate housing programs and rarely securing independent housing. Participants described the family, friends, and acquaintances who housed them during reentry as overextended and vulnerable. Implications for policy and practice are explored. © The Author(s) 2020.
Keywords: dept.swk; peer-reviewed

The Effects of Length of Residence and Exposure to Violence on Perceptions of Neighborhood Safety in an Urban Sample. - Guo, Monica; O'Connor Duffany, Kathleen; Shebl, Fatma M; Santilli, Alycia; Keene, Danya E (Journal of Urban Health, 2018)
Perceptions of neighborhood safety shape the well-being of individuals and communities, affecting neighborhood walkability, associated physical activity behaviors, and health conditions. However, less is known about the factors that determine perceptions of safety. One factor that may affect perceptions of neighborhood safety is the length of time someone has lived in their neighborhood. We use a representative, adult sample of urban low-income residents from the 2015 New Haven Health Survey (n = 1189) to investigate the associations between length of residence (new residents of < 1 year in neighborhood versus longer-term residents of 1 or more years in neighborhood) and perceptions of neighborhood safety (whether feeling unsafe to walk at night). We then examine the potential moderating effect of exposure to neighborhood violence on these associations. We find that the association between length of residence and perceived safety differs by exposure to neighborhood violence. Among those unexposed to neighborhood violence, longer-term neighborhood residents were more likely to feel unsafe compared to new residents (OR = 2.03, 95% CI 1.19, 3.45). Additionally, the effect of exposure to violence on feelings of safety was larger for new residents (OR = 9.10, 95% CI 2.72, 30.44) compared to longer-term residents (OR = 1.88, 95% CI 1.28, 2.77). Our findings suggest that length of residence may have implications for feelings of safety, and that experiences of violence may uniquely contribute to feelings of unsafety among new residents. These findings hold implications for interventions and policy efforts aimed at neighborhood safety improvements through community development, housing, or city urban planning initiatives, particularly for new neighborhood residents or those who experience neighborhood violence.
Keywords: *Exposure to Violence/px [Psychology]; *Exposure to Violence/sn [Statistics & Numerical Data]; *Poverty/px [Psychology]; *Poverty/sn [Statistics & Numerical Data]; *Residence Characteristics/sn [Statistics & Numerical Data]; *Safety/sn [Statistics & Numerical Data]; *Urban Population/sn [Statistics & Numerical Data]; Adult; Age Factors; Aged; Exposure to Violence; Exposure to violence; Female; Humans; Length of residence; Male; Middle Aged; Neighborhood; Perceptions of safety; Poverty; Residence Characteristics; Residential stability; Safety; Urban Population; Violence; Young Adult; adult; age; aged; demography; dept.pch; exposure to violence; female; human; male; middle aged; peer-reviewed; poverty; psychology; safety; urban population; young adult

Availability, accessibility, utilization: n-depth interviews with food insecure residents and emergency food providers in new haven, CT - Carroll, Grace; Keene, Danya; Santilli, Alycia; Johannes, Joy; Ickovics, Jeannette; Duffany, Kathleen O’Connor (Journal of Hunger & Environmental Nutrition, 2019)
Approximately 34% of residents from New Haven’s six lowest-income neighborhoods are food insecure, significantly higher than the rest of Connecticut and country (both approximately 12%). To understand the availability, accessibility, and utility of emergency food programs, we conducted 34 semi-structured qualitative interviews with 20 food insecure residents and 14 emergency food providers. Many depend on food programs as a long-term strategy of supplementing groceries rather than a temporary solution in emergency situations; providers are struggling to meet this demand. Transportation and time are barriers to accessing food from programs. Policies and food programs should focus on disseminating accurate information, streamlining policies and practices, and supporting and expanding food programs to meet population need.
Keywords: Food insecurity; adult; article; community health; community-based participatory research; dept.pch; emergency; emergency food programs; food insecurity; food pantries; human; interview; participatory research; peer-reviewed; public health; resident; soup kitchen; soup kitchens